Physical model of serum supplemented medium flow in organ-on-a-chip systems - Viesturs Šints; Jānis Cīmurs; Mihails Birjukovs; Ivars Driķis; Karīna Goluba; Kaspars Jēkabsons; Vadims Parfejevs; Una Riekstiņa; Gatis Mozoļevskis; Roberts Rimša; Guntars Kitenbergs (PLoS ONE, 2025)
Creating a physiologically relevant shear stress in organ-on-a-chip (OOC) devices requires careful tailoring of microfluidic flow parameters. Currently, it is fairly common to use a simple approximation assuming constant viscosity, even for serum-based media. Here, we show that a popular nutrient solution (Dulbecco’s Modified Eagle Medium supplemented with Fetal Bovine Serum) requires a more complex treatment (i.e., is a non-Newtonian fluid), with observed shear stress values significantly greater than reported in literature. We measure the rheology of the solutions and combine it with a 3-dimensional flow field measurement to derive shear stress at the channel surface. We verify the experiments with numerical simulations, finding good agreement and deriving flow properties. Finally, we provide relevant expressions for the shear stress approximation, suitable for development of OOC devices with various geometries.